MODIFIKASI MODEL RENKO UNTUK MEMPREDIKSI POLA PENGENDAPAN LUMPUR AKTIF DI SEDIMENTASI KEDUA - Ignasius Dwi Atmana Sutapa (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
The aim of this research is to gain the best activated sludge settling models in the final sedimentation. This is important for describing settling behavior of tropical Indonesian sludge. Sample sludge for this research was derived from the textile wastewater treatment. Experimental data were collected from batch settling test with 1000 ml cylinder glass. The test record complete batch sludge settling curves with initial concentration of about 4000 mg/L. To set up an experiment at lower sludge concentration, part of the sludge in the device was subsequently replaced by supernatant and a new settling curve was recorded. This procedure repeated until ten settling curves were recorded. The storage and settling experiments were performed at room temperature. In order to build appropriate models structure, all experimental settling data was converted. This experiment used the basic formulation models proposed by Renko, which identified settling of the sludge blanket interface as a function of time. This model described the relationship between settling sludge blanket interface and sludge concentration and settling time. Results of this research showed that these parameters were of α:0,0039; β:-0,3345; C:0,00028. The curves revealed that the models could follow the behavior of settling sludge. It proved with minimal MSE of 0,008. This value meant that the models had a high validity in explaining the experimental behavior. These results certainly beneficial for improving the wastewater treatment system for predicting sludge settling behavior in the secondary sedimentation process.